2021
DOI: 10.1155/2021/5573357
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Alleviates the Toxicity of High Nicotinamide Concentrations in Oocytes: Potential Interaction with Nicotinamide Methylation Signaling

Abstract: Despite the numerous studies on melatonin and nicotinamide (NAM, the active form of vitamin B3), the linkage between these two biomolecules in the context of signaling pathways regulating preimplantation embryo development has not yet been investigated. In this study, we used bovine oocyte model to elucidate the effect of melatonin on the developmental competence of oocytes under the stress of high NAM concentrations. Results showed that NAM (20 mM) administration during in vitro maturation (IVM) significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 52 publications
(79 reference statements)
4
11
0
Order By: Relevance
“…Counting the blastocyst inner cell mass (ICM) and trophectoderm (TE) cells have been used as indicators of cultured blastocyst quality, known as the CDX2-based differential staining assessment [ 21 , 22 ]. As shown in Figure 3 , the numbers of the total cells and TE cells per blastocyst were significantly higher in the VA-supplemented group (171.32 ± 5.97 and 123.42 ± 3.93, respectively) than the untreated control (157.47 ± 5.38 and 108.68 ± 4.59, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Counting the blastocyst inner cell mass (ICM) and trophectoderm (TE) cells have been used as indicators of cultured blastocyst quality, known as the CDX2-based differential staining assessment [ 21 , 22 ]. As shown in Figure 3 , the numbers of the total cells and TE cells per blastocyst were significantly higher in the VA-supplemented group (171.32 ± 5.97 and 123.42 ± 3.93, respectively) than the untreated control (157.47 ± 5.38 and 108.68 ± 4.59, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Differential staining of TE and ICM cells was performed as previously stated [ 21 ]. In brief, fixed blastocysts (20 per group) were washed in DPBS and permeabilized with 0.25% Triton X-100 for 20 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…MT-adjusted Nrf2 signaling decreased ROS in COCs and promoted swine ( 63 ) and mouse ( 64 ) oocyte IVM ( Figure 4B ). MT inhibited nicotinamide methylation signaling, promoting bovine oocyte IVM ( 65 ). In addition, MT is also involved in the Notch signaling pathway ( 66 ), the H4K16 deacetylation pathway ( 43 ), and the mTOR pathway ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that 10 mM NAM treatment in the IVF medium of bovine-fertilized embryos for 3 h reduced ROS in embryonic cells and significantly increased sirtuin1 expression and the blastocyst formation rate, indicating that NAM enhanced the developmental competence of bovine embryos in vitro via antioxidant activity [ 47 ]. However, a study showed that 20 mM NAM caused ROS accumulation and mitochondrial dysfunction in bovine oocytes, impairing oocyte maturation and embryonic developmental potential [ 48 ] Furthermore, in a review, investigators have pointed out that 5 mM NAM has a positive effect on the viability and replication of cells, but NAM exceeding 20 mM causes cell apoptosis [ 49 ]. The results of our study suggested that 5 mM may be an appropriate concentration for NAM supplementation in vitro, which improved oocyte maturation and fertilization in mice.…”
Section: Discussionmentioning
confidence: 99%